MOHR IN BANGLADESH (FIXATION, EFFECTS AND RECOMMENDATIONS) - Kabir, Humayoun; Sayeed Munna, Abu; Alam, Dr. Tasnim; Hasan Romel, Mahadi (IJRDO - Journal of Social Science and Humanities Research, 2017)
Mohr is one of the main features of Islamic marriages. And, without which a Muslim marriage can’t be solemnized. It is ordained that it should be given with a willing mood as a gift to that very female whom a person is going to marry. But most of the time, it is seen that this right of a woman is curtailed before or after the marriage. It is very obvious that sometimes the amount of Mohr is fixed whimsically by both the parties. Even, it is gauged beyond the means of the groom. It becomes a great problem when a marriage is ended with dissolution of marriage. The divorced wife never gets her proper right of Mohr without hurdle. It happens for several visible reasons. Most importantly, two factors that are very responsible for these are dower isn’t prompt with the reasonable amount not beyond the affordability of the groom and the natural instinct to escape the liability and obligations to pay the actual amount. This is how the number of cases relating non-payment of dower is a burning question for our judicial system of Family Courts. I have tried to figure out the easier solution to this phenomenon. It will surely lessen the problems faced by the parties for the payment of dower mostly in case of dissolution of marriage. There are some recommendations to pave the way to the right of dower of a woman to be ensured.